ITACARE-P/SIGG/SIGOT/SICGE position paper on elderly cardiac patient referral to cardiac rehabilitation - Francesco Giallauria; Angela Sciacqua; Alessandra Pratesi; Claudio De Lucia; Dario Leosco; Enrico Occhiuzzi; Angelo Scuteri; Andrea Ungar; Carlo Vigorito; Francesco Fattirolli; Samuele Baldasseroni; Luigina Guasti; et al. (International Journal of Cardiology. Cardiovascular Risk and Prevention, 2025)
The Italian Association for Cardiovascular Rehabilitation and Prevention (ITACARE-P) together with the Società Italiana di Gerontologia e Geriatria (SIGG); Società Italiana di Geriatria Ospedale e Territorio (SIGOT); SICGE, Società Italiana di Cardiologia Geriatrica (SICGE) released a joint position paper to guide referrals of elderly cardiovascular patients discharged from Geriatric wards to Cardiac Rehabilitation (CR) facilities. The document provides rationale and operative recommendations for appropriateness (i.e. qualifying diagnosis) and priority criteria to overcome mismatch between potential demand and effective supply of CR programmes. In case of no-referral due to logistic restraints, the document recommends the adoption of best alternatives to CR for disability reduction, better prognosis, and improvement of quality of life. The joint position paper is also aimed at promoting the consideration of Geriatric Medicine as a potential stakeholder of CR.